2023
DOI: 10.1108/jfbm-01-2023-0008
|View full text |Cite
|
Sign up to set email alerts
|

Responsible leadership practices in the hospitality sector family businesses: evidence from an emerging market

Abstract: PurposeThe study aims to find out the extent to which hospitality sector family-owned businesses in Egypt feel committed to responsible leadership practices and subsequently meet their stakeholders' expectations.Design/methodology/approachThe authors conducted semi-structured interviews with 24 owners of family restaurants in Egypt. Thematic analysis was undertaken on the collected data resulting in four major themes.FindingsThe authors find that the four dimensions (aggregation of virtuousness, stakeholder in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 82 publications
1
19
0
Order By: Relevance
“…Given the criticality of effective talent management practices in the hospitality sector (Bagheri et al, 2020;Kravariti et al, 2021;, the fragmented research on family business in the Arab region (Samara, 2021;Mousa and Arslan, 2023) and the limited number of empirical studies on the psychological contract in the hospitality sector (Blomme et al, 2010;Erkutlu and Chafra, 2016), the current paper aims to fill these gaps in the extant literature. The main objective of our study is to investigate the role of talent management practices in family-owned hotels in Sharm El-Sheikh (Egypt) to stimulate both family and non-family employees to fulfil the psychological contract.…”
Section: Psychological Contract Of Employeesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the criticality of effective talent management practices in the hospitality sector (Bagheri et al, 2020;Kravariti et al, 2021;, the fragmented research on family business in the Arab region (Samara, 2021;Mousa and Arslan, 2023) and the limited number of empirical studies on the psychological contract in the hospitality sector (Blomme et al, 2010;Erkutlu and Chafra, 2016), the current paper aims to fill these gaps in the extant literature. The main objective of our study is to investigate the role of talent management practices in family-owned hotels in Sharm El-Sheikh (Egypt) to stimulate both family and non-family employees to fulfil the psychological contract.…”
Section: Psychological Contract Of Employeesmentioning
confidence: 99%
“…, 2021; Mousa et al. , 2022), the fragmented research on family business in the Arab region (Samara, 2021; Mousa and Arslan, 2023) and the limited number of empirical studies on the psychological contract in the hospitality sector (Blomme et al. , 2010; Erkutlu and Chafra, 2016), the current paper aims to fill these gaps in the extant literature.…”
Section: Introductionmentioning
confidence: 99%
“…Their operations are influenced by personal values, dominant social norms and the relationship between family influence and firm growth depends on the institutional context of the family firm (Soleimanof et al, 2018). Mousa and Arslan (2023) found that family businesses having greater engagement with trading communities are more likely to be part of intercorporate ownership networks in these communities, which have shared features (e.g. language, religion, caste and region) and common values.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Family firm owners mostly tend to create a sense of cohesion and loyalty by encouraging member conformity and groupness, which creates a dysfunctional inertia that severely constrains exploitation and exploration of talent and knowledge of diverse members and that may possibly lead to elimination of learning necessary to stimulate entrepreneurship (Mousa et al, 2023). In the presence of democracy, rule of law, political stability and effective governance, family firms have a better chance to achieve long‐term economic and socio‐affective family goals than in a context where institutional uncertainty prevails and can deter firm growth (Mousa & Arslan, 2023; Soleimanof et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation